Civilianising specialist units: Reflections on the policing of cyber-crime. (September 2021) - Whelan, Chad; Harkin, Diarmaid
Civilianisation refers to utilising non-sworn personnel to perform certain roles within police organisations. While the civilianisation of policing has been examined in a variety of contexts, it has generally been in relation to attempts to improve police efficiency. The current literature is much less focused on efforts to intentionally seek out civilians to improve police effectiveness, which, we suggest, is likely to apply in the case of police responses to cyber-crime. Using empirical data collected with three specialist cyber-crime units in Australia, we explore the arguments for and against civilianising cyber-crime units as a strategy to improve police capacity, as reported by police and civilian members of these units. We consider these arguments in relation to a broader debate as to whether it is better to improve police capacity by employing civilian experts or attempt to develop greater expertise on cyber-crime among police.